Uma nova abordagem de mapeamento e localização simultâneo planar utilizando sensores RGB-D baseada em subtração de objetos - Souto, Leonardo Angelo Virgínio de (2016)
Abstract This paper aims to present a novel approach in planar RGB-D SLAM, here called Object Subtraction SLAM (OS-SLAM), using only low-cost RGB-D sensors such as the Microsoft Kinect. Our approach subtracts objects from the 3D environment and creates a clean 3D map projecting estimated planes without identified objects encountered along the mapping procedure aiming to increase accuracy. To validate our approach we performed four experiments, three in a real environment and one with an open dataset comparing them with other state-of-the-art algorithms. The algorithms were applied to a TurtleBot 2 platform which has a RGB-D sensor as its main sensor. The results demonstrated the efficiency on generated a clean and accurate map using the OS-SLAM algorithm.